Clinical and laboratory profiles of patients with early spontaneous healing in cutaneous localized leishmaniasis: a historical cohort study - Carla Oliveira-Ribeiro; Maria Inês Fernandes Pimentel; Raquel de Vasconcellos Carvalhaes Oliveira; Aline Fagundes; Maria de Fatima Madeira; Cintia Xavier Mello; Eliame Mouta-Confort; Claudia Maria Valete-Rosalino; Erica de Camargo Ferreira Vasconcellos; Marcelo Rosandiski Lyra; Leonardo Pereira Quintella; Liliane de Fatima Antonio; et al. (BMC Infectious Diseases, 2017)
Abstract Background Skin ulcers in American cutaneous leishmaniasis (ACL) may heal spontaneously after months/years. However, few cases may present quick heal even during diagnosis procedure (early spontaneous healing- ESH). The main objective of this study was to compare ESH patients with cases requiring specific treatment [non-ESH (NESH)]. Methods A historical cohort study of ACL patients (n = 445) were divided into 2 groups: ESH – spontaneously healed patients (n = 13; 2.90%), and NESH- treated patients (n = 432; 97.10%). We compared clinical and laboratorial findings at diagnosis, including the lesion healing process. Results ESH patients had a higher percentage of single lesions (p = 0.027), epithelialized lesion on initial examination (p = 0.001), lesions located in the dorsal trunk (p = 0.017), besides earlier healing (p < 0.001). NESH presents higher frequency of ulcerated lesions (p = 0.002), amastigotes identified in histopathology exams (p = 0.005), positive cultures (p = 0.001), and higher positivity in ≥3 parasitological exams (p = 0.030). All ESH cases were positive in only a single exam, especially in PCR. Conclusions ESH group apparently presented a lower parasitic load evidenced by the difficulty of parasitological confirmation and its positivity only by PCR method. The absence or deficiency of specific treatment is commonly identified as predisposing factors for recurrence and metastasis in ACL. However, due to the drugs toxicity, the treatment of cases which progress to early spontaneous healing is controversial. ESH patients were followed for up to 5 years after cure, with no evidence of recrudescence, therefore suggesting that not treating these patients is justifiable, but periodic dermatological and otorhinolaryngological examinations are advisable to detect a possible relapse.